Pictures of you ebook A novel. - Grey, Emma (Zibby Publishing, 2024)
A PEOPLE Magazine's Best Book of November 2024 A November 2024 Book of the Month Selection A USA Today Bestseller What would you do if you could start over? Imagine having a second chance with the one you never forgot. From the author of the global breakout bestseller The Last Love Note comes the story of a young woman struggling to piece her life back together in the wake of a tragic accident, and the man who gives up everything to help her. Evie Hudson should be grieving her dead husband, but since the car crash that claimed his life and landed her in the hospital, she can't remember him at all. The only person who can help her piece her past together is her high-school best friend Drew Kennedy. When snippets of her memory start falling into place, Evie wonders exactly how she ended up in a life that couldn't be further from the one she dreamed of. This time around, she's seeing all the things she missed—and the life she gets to choose . . . again.